An Investigation of Water Quality of Tajan River and Its Impact on Caspian Sea (Mazandaran Province North of I.R. Iran) - Mehrdadi, Nasser; Bagvand, A. (Asian Journal of Chemistry, 2010)
To design and implement monitoring programs for Tajan river water, factors such as frequency of sampling, analytical methods, site selection and criteria for water use area, were defined accordingly. A monitoring station was selected upstream of the river, inside Sari City and downstream close to Caspian Sea (delta). Samples were collected in 500 mL sterilized bottles on a monthly basis for physical, chemical and microbiological analysis. Sampling and analyses were carried out in accordance with standard methods. The results of water quality at different sampling locations show a moderate range of 7.6-8.2 pH. Total dissolved solids (TDS) are in the range of 350-1100 mg/L and at Delta up to 10800 mgIL. Maximum values for BOD and COD are 18 and 53 mg/L; maximum value of nitrates is 2.6 mg/L. The results show that the river quality is in moderate range. However, the presence of faecal-coliforms is indicative of the presence of domestic waste in the river water.